Repetitive Hyperbaric Oxygenation Attenuates Reactive Astrogliosis and Suppresses Expression of Inflammatory Mediators in the Rat Model of Brain Injury. (20th April 2015) - Lavrnja, Irena; Parabucki, Ana; Brkic, Predrag; Jovanovic, Tomislav; Dacic, Sanja; Savic, Danijela; Pantic, Igor; Stojiljkovic, Mirjana; Pekovic, Sanja
Abstract : The exact mechanisms by which treatment with hyperbaric oxygen (HBOT) exerts its beneficial effects on recovery after brain injury are still unrevealed. Therefore, in this study we investigated the influence of repetitive HBOT on the reactive astrogliosis and expression of mediators of inflammation after cortical stab injury (CSI). CSI was performed on male Wistar rats, divided into control, sham, and lesioned groups with appropriate HBO. The HBOT protocol was as follows: 10 minutes of slow compression, 2.5 atmospheres absolute (ATA) for 60 minutes, and 10 minutes of slow decompression, once a day for 10 consecutive days. Data obtained using real-time polymerase chain reaction, Western blot, and immunohistochemical and immunofluorescence analyses revealed that repetitive HBOT applied after the CSI attenuates reactive astrogliosis and glial scarring, and reduces expression of GFAP (glial fibrillary acidic protein), vimentin, and ICAM-1 (intercellular adhesion molecule-1) both at gene and tissue levels. In addition, HBOT prevents expression of CD40 and its ligand CD40L on microglia, neutrophils, cortical neurons, and reactive astrocytes. Accordingly, repetitive HBOT, by prevention of glial scarring and limiting of expression of inflammatory mediators, supports formation of more permissive environment for repair and regeneration.